Participation of the immune response and oxidative stress in alcoholism and liver cirrhosis due to alcohol - Leonardo S. Juárez-Chávez; José L. Pérez-Hernández; Abigail Hernández-Barragán; Zaira Medina-Avila; Marisela Hernandez-Santillan; Moisés Martínez-Castillo; Fátima Higuera-De la Tijera; Gabriela Gutiérrez-Reyes (Annals of Hepatology)
Introduction and Objectives: The spectrum of alcoholic liver disease (ALD) includes steatosis, steatohepatitis, alcoholic hepatitis, fibrosis, cirrhosis, and hepatocellular carcinoma. The pathophysiology of liver damage due to chronic alcohol consumption is complex. It is partly a result of reactive oxygen species (ROS) and reactive nitrogen species (RNS), products of oxidative stress, which is one of the mechanisms that will activate the immune system creating a pro-inflammatory state, increasing the levels of several cytokines (TNF-α, IL-1, IL-6, IL-8, MCP-1 and TGF-1). Objective: To study oxidative stress and the production of proinflammatory cytokines that intervene in the different stages of liver damage due to alcohol (alcoholism, alcohol-related liver cirrhosis, and alcoholic hepatitis). Material and Patients: A cross-sectional, prospective, and analytical study that included patients from the Gastroenterology service and donors from the Blood Bank. Patients at different stages of the disease and a control group of healthy subjects (blood bank donors) were included. They were divided into 4 groups: Alcoholism (OH), alcoholic liver cirrhosis (CiOH), alcoholic hepatitis (HA), and healthy controls (CT). From each participant, 20 ml of peripheral blood was obtained for the relevant determinations. Normally distributed data were obtained and ANOVA and orthogonal analyses were performed to detect group differences. A U-Mann Whitney test was used. P < 0.05 was taken as a significant difference. Results: 236 subjects were included: 67 patients in OH group; 40 patients with CiOH; 39 patients with Alcoholic Hepatitis (AH), and 90 subjects CT. The gender distribution in patients with ALD (CiOH, and HA) was 77.5% men and 22.5% women. The average alcohol consumption was 376.6±151.6 grams. The CiOH and HA groups presented alterations in platelets, bilirubin, and cytolysis markers at the expense of AST with a significant difference (p<0.05). Regarding oxidative stress, lipoperoxidation was greater in patients with chronic disease (CiOH) and protein damage (protein carbonyls) was greater in HA with p<0.05. Regarding cytokines and chemokines, TNF-α presented a higher level in CiOH and HA (p<0.5), IL-6 presented an elevation in CiOH and HA (p<0.05); IL-10 was elevated in OH, CiOH and HA, MCP-1 and IL-8 showed greater elevation in HA, p<0.05. Conclusions: Oxidative stress and the elevation of proinflammatory cytokines and chemokines have different behaviors in the various stages of alcohol liver disease, which influences the progression and prognosis of the disease. These findings could be considered as possible therapeutic targets.